Pengembangan UMKM dengan Cara Branding dan Pembuatan Akun Media Sosial Instagram di Desa Tambak Lekok, Desa Jatirejo dan Desa Tampung - Ardica Karunia Pradana; Maytita Tri Hardiyanti; Zulfa Aji Rani Isnuitama; Rahayu Mardikaningsih; Mila Hariani; Didit Darmawan; Rommy Hardyansah; Dharma Setiawan Negara (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This community service is related to the development of MSMEs that use branding strategies. Branding can include several important aspects that help strengthen the brand's identity and position in the market. Strong branding makes the brand more easily recognized and remembered by consumers, helps differentiate it from competitors. A strong brand can build emotional connections with customers, resulting in long-term loyalty. Unique branding helps differentiate a product or service from those offered by competitors, creating a competitive advantage.